The Needs Fulfillment of Medical and Specialist Doctors in West Nusa Tenggara, Indonesia - Dumilah Ayuningtyas; Anwar Fachry; Sandra Barinda; Sri Windiarti; Nurul Saptorini Rahmadhani; Muhammad Sapoan Hadi; M Misnaniarti; Ni Nyoman Dwi Sutrisnawati (Universitas Aisyah Pringsewu, 2021)
One of the challenges in improving health services in Indonesia is the uneven number and distribution of health workers in some areas, especially doctors and specialist doctors. Therefore, the aim of this study was to review the conduciveness and support of the policy environment towards meeting the needs of specialist doctors in West Nusa Tenggara (NTB) Province, Indonesia. This study was the narrative review method. Keywords used are environmental policy, specialist doctor, and remote area. Critical appraisal was performed by utilizing the PRISMA method. This study showed that there is political support from the Central and Regional Governments. However, several aspects are still recognized negatively, aspects of national policies related to incentives and facilities. Regional Government Policies are considered not sufficiently significant to improve the availability of doctors and specialist doctors, especially in terms of the advocacy mechanisms. This matter impacts the lack of doctors and specialist doctors’ interest to be placed in remote areas. The policy environment towards meeting the needs of a specialist doctors in West Nusantara Tenggara (NTB) was enough conducive and supportive. It still needs improving coordination mechanisms among institutions and providing advocacy channels, which are crucial to support the effectiveness of meeting the needs of specialist doctors’ policies.Abstrak: Salah satu tantangan dalam meningkatkan pelayanan kesehatan di Indonesia adalah belum meratanya jumlah dan distribusi tenaga kesehatan di beberapa daerah, terutama dokter dan dokter spesialis. Oleh karena itu, penelitian ini bertujuan untuk mengkaji kondusifitas dan dukungan lingkungan kebijakan terhadap pemenuhan kebutuhan dokter spesialis di Provinsi Nusa Tenggara Barat (NTB), Indonesia. Penelitian ini menggunakan metode review naratif. Kata kunci yang digunakan adalah kebijakan lingkungan, dokter spesialis, dan daerah terpencil. Critical appraisal dilakukan dengan menggunakan metode PRISMA. Studi ini menunjukkan adanya dukungan politik dari Pemerintah Pusat dan Daerah. Namun demikian, beberapa aspek masih diakui secara negatif, aspek kebijakan nasional terkait insentif dan fasilitas. Kebijakan Pemerintah Daerah dinilai belum cukup signifikan untuk meningkatkan ketersediaan dokter dan dokter spesialis, terutama dari sisi mekanisme advokasi. Hal ini berdampak pada minimnya minat dokter dan dokter spesialis untuk ditempatkan di daerah terpencil. Lingkungan kebijakan untuk memenuhi kebutuhan dokter spesialis di Nusantara Tenggara Barat (NTB) cukup kondusif dan mendukung. Masih perlu perbaikan mekanisme koordinasi antarlembaga dan penyediaan jalur advokasi yang sangat penting untuk mendukung efektivitas pemenuhan kebutuhan kebijakan dokter spesialis.